Synthesis of Ni(II), Cu(II) and Zn(II) coumarin-3-carboxilic acid derivates and their and their physical-chemical properties (Research, Society and Development, 2021)
In the search for new drugs, coumarins are an important class of compounds due to their chemical and biological properties, such as their potential to reduce cancer, diabetes, and cardiovascular diseases. They are heterocyclic compounds that contain oxygen in their structure and are found in plants.To improve the chemical and biological properties of the coumarin-3-carboxilic acid, were prepared metal transition complexes of Cu(II), Ni(II) and Zn(II) of coumarin-3-carboxilic acid by a new synthetic route. All complexes were characterized by Ultraviolet (UV), Infrared (FTIR), and Raman spectroscopy; Scanning electronic microscopy (SEM); X-Ray diffraction (XRD), as well as conductivity and elemental analysis. Electron microscopy and X-ray analysis showed that the degree of crystallinity of the complexes changes when compared with the precursor, 3-carboxy-coumarin acid, and the degree of crystallinity depends on the nature of the metal ion attached to coumarin. In addition, the antioxidant action of the complexes was evaluated by the DPPH method, and the results showed a higher activity of the complexes when compared with the precursor, suggesting that these complexes may present biological properties of interest.